DETERMINAN STATUS UNMET NEED FOR LIMITING BIRTH PADA WANITA USIA SUBUR BERSTATUS KAWIN DI JAWA BARAT TAHUN 2017 - Valencia Shabrina Putri; Siskarossa Ika Oktora (Jurnal Kependudukan Indonesia, 2020)
Rapid annual population growth in West Java, the province with the highest population in Indonesia, is concerning due to its effect that could lead to population explosion in the future. One of the reasons for this rapid growth is caused by a high birth rate. However, the implementation of the family planning program to control the birth rate faced a challenge in terms of unmet need for family planning in women of reproductive age. Unmet need for limiting birth has a more critical role in total unmet birth control need. This study aims to determine factors that affect the unmet need for limiting birth at married women of reproductive age in West Java Province in 2017 using binary logistic regression. Results indicated that women's age, women's education level, husband's education level, and residence significantly affected unmet need status for limiting birth. Also, the tendency of unmet need for limiting birth is greater for women aged 35-49 years, has education junior high school and above, the husband has under junior high school education and living in the rural area.